PKM Pembangkit Listrik Tenaga Hybrid di Desa Sabiyan Kabupaten Bangkalan - Riza Alfita; Rosida Vivin Nahari; Mirza Pramudia; Kartika (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The Community Partnership Program (PKM) is a community service program that carried out in the village assisted by the Electrical Engineering Study Program at the University of Trunojoyo Madura. the program is a continuation of the Real Work Lecture program (KKN) which is carried out in the Even semester 2019/2020 involving students, as well as village officials. The village of Sabiyan is located on the coast of Madura where the average population still relies on electricity for daily activities. The problems faced by the people of Sabiyan village Bangkalan Regency are: the people of Sabiyan Village do not yet have the knowledge and skills to utilize renewable energy, lighting facilities are still limited so that not all citizens can get electricity, the price of Basic Electricity Tariff (TDL) is higher so it is necessary renewable energy reserves. With these problems, it is necessary to have a hybrid power plant training. Based on the results of the pre-test conducted on the training participants, the average value was 62.50 and the post-test value was 75.83, with a paired sample correlation of -13.33 so that it could be concluded that there was an increase in knowledge after the training was held